Leg Length Discrepancy - Berianto Agustian; Tertianto Prabowo; Dian Marta Sari (Indonesian Journal of Physical Medicine & Rehabilitation, 2022)
ABSTRACT Leg length discrepancy (LLD) is a condition of length differences in the lower extremity, caused by variety of factors, both congenital and acquired. Measurement using measuring tape, block test, and supine-tositting test based on bony landmarks is considered less accurate than imaging techniques. Measuring LLD can be difficult in certain cases such as obesity, leg deformities, and post arthroplasty. Individuals will develop biomechanical strategies to compensate inequality of leg when standing, walking, andrunning on their feet, ankles, knees, hip, and or pelvis to minimize energy consumption. It can causes several complications, including osteoarthritis, functional scoliosis, intervertebral disc degeneration, stress fractures, cardiovascular and neuromuscular problems. Management varies from wearing a shoelift, relieve muscle and joint contracture, and surgical procedures. This paper was written to review measurement technique, biomechanical compensation strategies, complication, and management of LLD from Physical Medicine and Rehabilitation point of view .Keyword: biomechanical compensation strategies, leg length discrepancy, lower extremity, management, measurement